Awareness and willingness to use pre-exposure prophylaxis for HIV prevention among men who have sex with men in Rwanda: findings from a web-based survey - Munyaneza, Athanase; Patel, Viraj V.; Gutierrez, Nataly Rios; Shi, Qiuhu; Muhoza, Benjamin; Kubwimana, Gallican; Ross, Jonathan; Nsereko, Etienne; Murenzi, Gad; Nyirazinyoye, Laetitia; Mutesa, Leon; Anastos, Kathryn; et al. (Frontiers in Public Health, 2024)
Introduction Pre-exposure Prophylaxis (PrEP) is a daily pill aimed at reducing HIV transmission risk when taken as prescribed. It’s highly recommended for high-risk Men who have sex with Men (MSM). This study aimed to assess PrEP awareness and willingness to use it among Rwandan MSM, a critical aspect given PrEP’s proven effectiveness. The findings are expected to inform policy decisions and further advance the implementation of PrEP strategies. Methods This is a cross-sectional study design that utilized a web-based survey conducted between April and June 2019 to assess awareness and willingness to use PrEP among sexually active MSM in Rwanda. A snowball sampling technique was used to recruit participants via social media such as WhatsApp and e-mail. Eligibility criteria included being sexually active, aged ≥18 years, self-identifying as MSM, residing in Rwanda, self-reported engagement in receptive or insertive anal sex in the last 12 months, and self-reported HIV-negative serostatus. We assessed two primary outcomes: PrEP awareness (having ever heard of PrEP) and willingness to use PrEP within one month of completing the survey. Multivariable logistic regression was performed to identify participant characteristics associated with PrEP awareness and willingness to use it. Results Out of 521 participants, the majority (73%) demonstrated awareness of PrEP. Factors linked to PrEP awareness included residing outside the capital, Kigali, being in the 18–29 age group, having higher education levels, perceiving a benefit from PrEP, and engaging in vaginal sex with a woman while using a condom in the last year. Additionally, 96% of participants expressed a strong willingness to use PrEP. Conclusion Rwandan MSM exhibits a high level of PrEP awareness, notably associated with factors like location, age, education, perceived benefits, and condom use. The study also revealed a strong willingness to use PrEP, indicating promising prospects for its adoption among this group. These findings highlight the need for targeted awareness campaigns, personalized interventions, and comprehensive sexual health education to promote PrEP adoption and strengthen HIV prevention efforts among Rwandan MSM.